STRATEGI KEPALA MADRASAH DALAM MENINGKATKAN KOMPETENSI SOSIAL GURU DI MTS AL KHOIRIYAH 2 MULYOREJO DALEGAN PANCENG GRESIK - Siska Zahrotul Hidayah; Muhammad Haris (Mudir : Jurnal Manajemen Pendidikan, 2022)
The strategy of the head of madrasa in improving the social competence of teachers but there are still many teachers who are less than optimal in communicating well. This social competence also affects the formation of student character and affects relations with the community. This study aims to answer several problem formulations: 1) What is the strategy of the head of madrasa in improving the social competence of teachers?. 2) What are the influencing factors in improving the social competence of teachers? This type of research includes qualitative research, which generates data and is analyzed using a descriptive method adapted to MTs. Al Khoiriyah 2 Mulyorejo. The data collected using interview, observation, and documentation techniques. The results of this study, that the strategy of the head of madrasa in improving the social competence of Mts teachers. Al Khoiriyah 2 Mulyorejo is a collaborative strategy. And in improving the social competence of teachers, the head of madrasah includes teachers in MGMP, Workshop, and IT Guidance. Not only that, once a month the head of the madrasah holds meetings and evaluations and involves teachers in community activities, namely Istighosah. That way the teacher can add insight and establish good friendship, thereby increasing interaction relations to the maximum. In accordance with the madrasa principal's strategy, several factors affect the teacher's social competence. The factors that influence in improving the social competence of teachers are the educational background of each teacher, the age of the teacher, experience in learning, influences from within and environmental conditions. As for the results of this study, it is recommended that in the future the madrasa head pays more attention to the problems that exist within the scope of the madrasa institution, especially in terms of good communication. So that teachers, staff, and students are able to apply it in everyday life to the fullest. And there needs to be a forum that bridges between teachers who take part in trainings with the intention of transmitting the knowledge that has been obtained to other teachers. So you can implement.